-5/6x-7/30x+1/5=-52

Simple and best practice solution for -5/6x-7/30x+1/5=-52 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5/6x-7/30x+1/5=-52 equation:



-5/6x-7/30x+1/5=-52
We move all terms to the left:
-5/6x-7/30x+1/5-(-52)=0
Domain of the equation: 6x!=0
x!=0/6
x!=0
x∈R
Domain of the equation: 30x!=0
x!=0/30
x!=0
x∈R
We add all the numbers together, and all the variables
-5/6x-7/30x+52+1/5=0
We calculate fractions
540x^2/4500x^2+(-3750x)/4500x^2+(-1050x)/4500x^2+52=0
We multiply all the terms by the denominator
540x^2+(-3750x)+(-1050x)+52*4500x^2=0
Wy multiply elements
540x^2+234000x^2+(-3750x)+(-1050x)=0
We get rid of parentheses
540x^2+234000x^2-3750x-1050x=0
We add all the numbers together, and all the variables
234540x^2-4800x=0
a = 234540; b = -4800; c = 0;
Δ = b2-4ac
Δ = -48002-4·234540·0
Δ = 23040000
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{23040000}=4800$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-4800)-4800}{2*234540}=\frac{0}{469080} =0 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-4800)+4800}{2*234540}=\frac{9600}{469080} =80/3909 $

See similar equations:

| 8(-3d+2=88 | | MA=X,mB=2X.mC=2X+30 | | 52x+12x=1912+92x | | 3x+4+2x=1 | | 3m=5(m+3)-5 | | 10x+35-8=57 | | 7n^2+15n-18=0 | | 12.43+0.09x=12.91-0.08x | | 2x^2-12x+118=0 | | 7(5x-2)=6(3x+1) | | 7(z+2)=14 | | 7y+3=3y+5=15y-12 | | (2x-7)/8+x=(2x+7)/2+7 | | 13-3=w | | 3-13=w | | 6x-3-4x-4=0 | | 15x+15=25 | | 2(3x+1=4x+2 | | 2f+5f+3-f=10(1)+9(0)+f+13 | | 23(x−6)=623(x-6)=6 | | 8(x-3)-(6+3x)=(-x+2)-5(5-x) | | 49^3x=343^2x+1 | | 45+17m=249 | | 29n-135=300 | | 8(x-3)-6+3x=(-3+2)-5(5-x) | | -4(1+4n)-2n=-2(-2+7n) | | 7y+2=3y+9=14y-9 | | 3(n-2)-5(n-1)=1 | | y+2y−6=0 | | -22=x-24 | | z+69= 4 | | -22=x—24 |

Equations solver categories